Matching and Bargaining in Dynamic Markets - Binmore, K. G.; Herrero, M. J. (Review of Economic Studies, 1988)
K. G. Binmore, M. J. Herrero; Matching and Bargaining in Dynamic Markets, The Review of Economic Studies, Volume 55, Issue 1, 1 January 1988, Pages 17–31,